Improving Mathematics Learning Outcomes of Fourth Grade Students of SD Negeri 4 Kontukowuna in Solving Story Problems Through Peer Tutor Learning and Using LKS - moharisah moharisah (Amanah: Jurnal Amanah Pendidikan dan Pengajaran, 2021)
The purpose of this study was to analyze the improvement of mathematics learning outcomes for fourth-grade students of SDN 4 Kontukowuna in solving story problems on the subject of mixed arithmetic operations through the implementation of peer tutoring and the use of worksheets. Classroom action research was carried out in the fourth grade of SDN 4 Kontukowuna with 25 students consisting of 11 male students and 14 female students. The study was carried out in two cycles covering planning, implementing actions, observing/evaluating, and reflecting. Each process is carried out in two meetings. Sources of data from students and teachers were obtained from the evaluation of learning outcomes, group work results, homework in each cycle, and observations about teacher and student activities. The results showed that in the first cycle, students who got a minimum score of 65.0 were 15 students (60.0%), while active students could communicate about 60.0% or about 15 students. These results are not satisfactory and not as expected. Therefore, it is necessary to do cycle II, and it turns out that the evaluation results in cycle II show that students who get a minimum score of 65.0 are 22 students (88.0%). In contrast, observing student activities shows that students who can do mathematical communication are around 80: .0 % or as many as 20 students. The conclusion is that peer tutoring and the use of worksheets can improve learning outcomes.